The “green wave” mode production on the two‐lane highways during the construction works time period - Berezhnoy, Аlexander; Grakovsky, Аlexander; Nesterov, Аlexey (Transport, 2007)
In the paper, the problem of a bi‐directional “green wave” mode production is considered for the vehicle flows motion on two‐lane highways during the conducting of construction works. The solution of the given task allows to develop practical recommendations for the sphere of the construction works management on two‐lane roads and country highways, and also to raise traffic control efficiency in the pointed conditions. The comparative analysis of possible traffic regulation modes for the set scheme of road construction works sites and the estimation of their efficiency is performed, the test of a hypothesis regarding the possibility of a bi‐directional “green wave” mode realization is carried out, and calculation of traffic lights signal control phases time is performed.First Published Online: 27 Oct 2010